2020
DOI: 10.3389/fcimb.2020.00407
|View full text |Cite
|
Sign up to set email alerts
|

Aedes Mosquito Salivary Components and Their Effect on the Immune Response to Arboviruses

Abstract: Vector-borne diseases are responsible for over a billion infections each year and nearly one million deaths. Mosquito-borne dengue virus, West Nile, Japanese encephalitis, Zika, Chikungunya, and Rift Valley Fever viruses constitute major public health problems in regions with high densities of arthropod vectors. During the initial step of the transmission cycle, vector, host, and virus converge at the bite site, where local immune cells interact with the vector's saliva. Hematophagous mosquito saliva is a mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 101 publications
1
41
0
Order By: Relevance
“…After 3 days of rest in a humid chamber at laboratory temperature, ticks were fed on C3H/HeN mice (15-20 nymphs per mouse) until full engorgement. Two weeks later, mice were sacrificed, and the numbers of Borrelia spirochetes in the earlobe, urinary bladder, heart tissue, and ankle joint were estimated by qPCR [82] and normalized to the number of mouse genomes [83] (primer and probe sequences in Supplementary Table S1). The level of gene knockdown was checked by qPCR in an independent experiment.…”
Section: Rna Silencing and Borrelia Transmissionmentioning
confidence: 99%
“…After 3 days of rest in a humid chamber at laboratory temperature, ticks were fed on C3H/HeN mice (15-20 nymphs per mouse) until full engorgement. Two weeks later, mice were sacrificed, and the numbers of Borrelia spirochetes in the earlobe, urinary bladder, heart tissue, and ankle joint were estimated by qPCR [82] and normalized to the number of mouse genomes [83] (primer and probe sequences in Supplementary Table S1). The level of gene knockdown was checked by qPCR in an independent experiment.…”
Section: Rna Silencing and Borrelia Transmissionmentioning
confidence: 99%
“…It is suggested that mosquito bite enhancement of virus infection is not related to interferon response suppression. Instead, host increased susceptibility is closely related to neutrophil-dependent inflammation after a bite [ 82 , 83 ]. Following a bite, mast cell degranulation markedly increases the expression of IL-1β, IL-6 and neutrophil-attracting chemokines such as CXCL1, CXCL2, CXCL3 and CXCL5.…”
Section: Participation Of Neutrophils and Neutrophil-associated Molecules In Flaviviral Diseasesmentioning
confidence: 99%
“…This route of pathogen transmission is vastly different from the vector-mediated natural infection and may lead to erroneous results of challenge studies. In comparison with other vector-borne disease models, studies of mosquito-borne and tick-borne diseases suggested that the needle-based transmission route does not fully recapitulate vector-mediated transmission, due to the absence of important immunomodulatory molecules contained in vector saliva [ 37 , 38 ] or by bypassing the natural route of host cell invasion which alters the resulting host immune response. Utilization of needle-based inoculation approach potentially leads to incomparable results to the vector-mediated transmission and immunological response observed in humans [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%